Knowledge creation capability, absorptive capacity, and product innovativeness. (22nd October 2013) - Su, Zhongfeng; Ahlstrom, David; Li, Jia; Cheng, Dejun
Abstract : This study focuses on the impact of knowledge creation capability and absorptive capacity on product innovativeness. Capabilities contribute through their uniqueness, their integration into effective configurations, and their deployment in response to external environment changes. Therefore, this study examines the individual (uniqueness) and interactive (integration) effects of knowledge creation capability and absorptive capacity on product innovativeness as well as how these effects vary in differing technologically turbulent contexts (deployment). Based on a survey of 212 Chinese firms, this study finds that in addition to their individually positive effects, knowledge creation capability and absorptive capacity have a synergistic effect on product innovativeness. Moreover, the individual effect of knowledge creation capability and the synergistic effect become stronger as technological turbulence increases, whereas the impact of absorptive capacity tends to be dampened by technological turbulence.